Development and validation of virtual patients for assessing history taking and communication skills among medical students - Mohd Salim, Nurul Ain; Azman, Azreen; Sulaiman, Puteri Suhaiza; Roslan, Nurhanis Syazni; Hod, Rafidah; Adam, Siti Khadijah (BioMed Central, 2026)
Background: The integration of virtual patients (VPs) into medical education is expanding globally, enhancing traditional training and supporting the development of clinical skills. In Malaysia, adoption is progressing, although dependence on imported platforms may compromise cultural and linguistic authenticity. We developed three culturally adapted VPs reflecting the local healthcare context. The VP application, featuring a custom virtual reality (VR) environment, 3-dimensional (3D) avatars and speech functions, was deployed on the Oculus Meta Quest 2 headset. This device provides an immersive, user-friendly experience, allowing students to interact with VPs via hand-held controllers. Methods: The developed VPs were assessed in terms of their content, face, construct, and concurrent validity, as well as the reliability for use in history-taking and communication skills assessment. Data analysis was performed using IBM SPSS Statistics software version 25. Results: The VPs showed acceptable content and face validity, indicating that the case design, interface, and simulated environment were appropriate and realistic. However, reliability and other validity measures, including construct validity and concurrent validity, were found to be limited. Conclusion: These findings may have been affected by factors such as small sample size, variability among students and examiners, limited scenario complexity, and technical issues related to speech recognition and system responsiveness. Addressing these limitations in future research could improve the generalizability of the results, while refinements in scenario design, artificial intelligence (AI) integration, and user interfaces are key to maximizing the pedagogical potential of VPs.